2016
DOI: 10.1016/j.bbr.2016.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Nest building is a novel method for indexing severity of alcohol withdrawal in mice

Abstract: Withdrawal after chronic ethanol (EtOH) affects body temperature, goal-directed behavior and motor function in mice and increases general central nervous system excitability. Nest-building tests have been used to assay these states but to this point have not been employed as measures of EtOH withdrawal severity. We first refined nest-scoring methods using a genetically heterogeneous stock of mice (HS/Npt). Mice were then made physically dependent following three days of chronic EtOH vapor inhalation to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…We aimed to have 10 mice per sex and ethanol treatment group for each experiment. We previously reported that this number of animals produced significant ethanol effects on nest building [22]. Mice were euthanized via CO 2 asphyxiation followed by cervical dislocation after the completion of behavioral testing.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We aimed to have 10 mice per sex and ethanol treatment group for each experiment. We previously reported that this number of animals produced significant ethanol effects on nest building [22]. Mice were euthanized via CO 2 asphyxiation followed by cervical dislocation after the completion of behavioral testing.…”
Section: Methodsmentioning
confidence: 99%
“…The schedule of nest scoring allowed for the observation of nest building deficits and tracking of recovery over time. The nest scoring methods are described in more detail elsewhere [22] and were derived from published descriptions [11,18]. Briefly, if the nesting material was untouched, or if some of it had been moved, a score of 0 or 1 was given, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations